IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR IPA KELAS V MATERI SIKLUS AIR BERBANTUAN MEDIA DIORAMA - Zahrotul Afifah, Maya; Listyani, Ivayuni; Sayekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This Classroom Action Research (PTK) was motivated by the low learning outcomes of science content students in class V of SD Negeri 02 Mojorejo. This research aims to determine the improvement in student learning outcomes through the application of the Problem Based Learning learning model assisted by diorama media. The research was carried out in class V of SD Negeri 02 Mojorejo with research subjects of 28 students. This research is a type of classroom action research (PTK) which was carried out over two cycles, and two meetings were held in each cycle. Each cycle consists of four stages, namely planning, implementation, observation and reflection. Data collection techniques in this research used test, observation, interview and documentation techniques. The results of research on pre-cycle measures showed that the percentage of classical completeness (12%) with an average score of 55 had increased in cycle I. In cycle I, the percentage of classical completeness of student learning outcomes was found to be (52%) with an average score of 73. In cycle II there was an increase with the percentage of classical completeness reaching (100%) with an average score of 89. Meanwhile, the percentage of classical completeness of student learning outcomes was skills in cycle I (82%) and increased in cycle II (92%). So the results of this research can be concluded that the application of the Problem Based Learning learning model assisted by diorama media can improve learning outcomes for class V of SD Negeri 02 Mojorejo for the 2023/2024 academic year